Breathy voice and low-register: A case of trading relation in Shanghai Chinese tone perception?. (September 2020) - Gao, Jiayin; Hallé, Pierre; Draxler, Christoph
In Shanghai Chinese as well as many other Wu dialects, breathy voice is a well-documented accompaniment of the low-register tone syllables with obstruent as well as sonorant onsets. But Shanghai Chinese is rapidly changing and the breathy voice associated with low-register tones tends to disappear in young speakers' productions. In this study, we asked whether breathy voice is nevertheless still perceived and whether it pushes tone identification toward low-register tones. We conducted forced-choice tone identification tests on young native listeners of Shanghai Chinese, using low–high register tone continua—from tone T3 (23) to tone T2 (34)—imposed on base syllables with either modal or breathy voice quality, and beginning with various onset consonants. We used continua constructed from either naturally produced or synthesized syllables. Our results show that breathy voice does bias tone identification responses toward the low-register tone T3. This result held for both synthesized and natural stimuli, except for the /m/-onset stimuli derived from naturally produced syllables. We propose that the phonetic change at issue—loss of breathiness in production—is not due to misperception but reflects the ever-stronger influence of Standard Mandarin Chinese. In other words, this particular case of sound change seems to be led by production rather than perception. It remains an open question whether this kind of sound change is only determined by sociolinguistic factors (here, the dominance of Mandarin Chinese) or is independently motivated by phonetic and/or phonological factors.